Thiosemicarbazone-based selective proliferation inactivators inhibit gastric cancer cell growth, invasion, and migration. Issue 12 (23rd October 2017) - Hu, Biao; Wang, Bo; Zhao, Bing; Guo, Qian; Li, Zhong-Hua; Zhang, Xin-Hui; Liu, Guang-Yao; Liu, Ying; Tang, Ying; Luo, Fan; Du, Ya; Chen, Ya-Xin; et al.
Abstract : A series of novel thiosemicarbazone derivatives were synthesized and evaluated for their antiproliferative activity against several tumor cell lines by MTT assay. Abstract : A series of novel thiosemicarbazone derivatives were synthesized and evaluated for their antiproliferative activity against several selected tumor cell lines of different origins using the MTT assay. The preliminary results indicated that the MGC-803 cell line was remarkably sensitive to all the synthesized compounds. Among this series, compound5n showed the best inhibitory activity with an IC50 value of 0.93 μM (about 10-fold more potent than3-AP ) against MGC-803. Further mechanism studies revealed that compound5n could obviously inhibit the proliferation of MGC-803 cells by inducing apoptosis and arresting the cell cycle at the S phase. Compound5n also showed marked inhibition of cell migration and invasion, without significant cytotoxicity against gastric epithelial immortalized GES-1 cells.